PENGEMBANGAN MEDIA LAGU EDUKASI BERBASIS GOOGLE SITES UNTUK MENINGKATKAN HASIL BELAJAR MATERI WUJUD ZAT DAN PERUBAHANNYA MUPEL IPAS KELAS IV SD MUHAMMADIYAH LEGOKKALONG PEKALONGAN - Nandadewi, Annisa Tribuana; Fathurrahman, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the teaching and learning process, learning media has an important role in creating efficient and effective learning. The learning media used must also vary so that students are more enthusiastic about learning. This is in accordance with the problems found in Class IV of SD Muhammadiyah Legokkalong, where the learning process has not used varied learning media. The purpose of this research is to develop educational song media based on google sites and test its feasibility and effectiveness. The method used is the Research and Development (R&D) method with the Borg and Gall development model which uses 8 stages including: (1) potential and problems; 2) data collection; 3) product design; 4) design validation; 5) design revision; 6) product trial; 7) product revision; 8) trial use. The data collection techniques used were test and non-test techniques. The results of this study indicate that the media developed is very feasible as evidenced by the assessment of material experts with a score of 85% and media experts with a score of 85.9%. The media developed also proved to be quite effective in improving student learning outcomes as shown by the N-Gain results of 0.684 or 68.4% which fell into the moderate category. The developed media also received positive responses from teachers and students with a result of 100%. The conclusion of this study is that educational song media based on google sites is very feasible and quite effective in learning IPAS grade IV at SD Muhammadiyah Legokkalong Pekalongan.